Welcome to the First Issue of PACMHCI EICS - Calvary, Gaelle (2017)
[Extract] It is our great pleasure to welcome you to the first issue of PACMHCI EICS, which features full papers appearing at the 9th ACM SIGCHI Symposium on Engineering Interactive Systems (EICS’17). The conference takes place in Lisbon, Portugal on 26-29 June, 2017. EICS gathers researchers that aim to improve the ways we build interactive systems. Building interactive systems is a multi-faceted and challenging activity, involving a plethora of different actors and roles. This is particularly true in the domain of HCI, where we continuously push the edge of what is possible, where there is a crucial need for adequate processes, tools and methods to build reliable, useful and usable systems that help people cope with the ever-increasing complexity of work and life. The primary goal of the EICS conference series is to provide a venue for novel and high quality contributions in this direction...